Analysis of Vaccine Distribution and Implementation in North Maluku: A Case Study at the Port Health offIce - Rukmina Hi. Barawes; Nani Supriyatni; Diah Merdekawati Surasno; Hadija Teapon; Muhammad Idris Lukman; Rizka Suciyati Buano; Widya Putri Avilliani (BIOSAINSTEK, 2026)
Vaccination is a highly effective public health intervention for preventing the spread of infectious diseases and reducing morbidity and mortality rates in the community. In this context, the Port Health Office (KKP) plays a crucial role in conducting vaccinations for travelers engaging in international travel and for other health-related purposes. This study aims to describe the distribution of vaccination participants based on regional characteristics and the types of vaccines administered at the Maluku Utara KKP in 2025. The research methodology used is an observational descriptive design, utilizing secondary data from vaccination service records recorded at the KKP from September to November 2025. A total of 843 vaccination participants were analyzed using total sampling, and data were analyzed descriptively through frequency and percentage distributions. The results showed that the majority of participants were women (55.9%), with Ternate City being the region with the highest number of participants, totaling 442 people, while Sula Islands Regency had the fewest, with only 3 participants. Regarding vaccine types, the combined meningitis meningococcal and polio vaccines were the most widely administered, with 621 services. This was followed by meningococcal meningitis and polio vaccines, each with 108 services. These findings indicate that vaccination demand in North Maluku mainly revolves around vaccines that are requirements for international travel, especially for Umrah pilgrims and travelers going abroad. Therefore, the vaccination services provided by the KKP support public health protection and fulfill international travel health requirements.